Emerging technologies in airway management: a narrative review of intubation robotics and anatomical structure recognition algorithms - Weixiong Chen; Yu Tian; Yingjie Wang; Lili Feng; Mannan Abdul; Shuangshuang Li; Wenxian Li; Yuan Han (BioMedical Engineering OnLine, 2025)
Abstract In recent years, the medical field has seen significant advancements in the field of robotics and artificial intelligence (AI). However, many healthcare professionals still find these technologies unfamiliar and complex, especially regarding their use during airway management. This review covers the current capabilities of robots and AI in tracheal intubation (TI), providing new insights that advocate for the broader adoption of these technologies to improve airway management. A literature review on robotics and AI in TI was conducted through searches in the PubMed, Web of Science, and IEEE Xplore databases. Drawing on a classification framework derived from expert opinions and existing literature, these studies are categorized into six key stages. Most of these technologies remain in the testing and validation phases, with only a few having reached commercialization. The primary goal of these robotic and AI systems is to enhance the success rate and operational efficiency of intubation while mitigating the persistent shortage of medical resources and supporting telemedicine. However, ongoing attention is required to address challenges such as high costs, a shortage of interdisciplinary talent, and ethical concerns related to medical bias and data security. Robots and AI are beginning to play a significant role in TI. Although many of these technologies remain in the theoretical stage of clinical application, their potential to enhance clinical practice is substantial, provided they are implemented as complementary tools that support rather than substitute the expertise of healthcare professionals. AI-powered robots show great potential as assistive tools for optimizing intubation maneuvers, whereas clinical decision-making (e.g., determining the necessity of intubation) remains under the supervision of physicians.